Management of Two-Wall Infra-Bony Defect with Platelet Rich Fibrin and Connective Tissue Graft Combination: A Case Report - Huseyin Gencay Keceli; Serdar Yucel Ozkan; Humerya Aydemir Turkal; Tolga Fikret Tozum (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
Background: Regenerative procedures offer a limited potential toward achieving a complete periodontal regeneration and today, there is not any single material that can be considered as 'gold standard' in infra bony defect treatment. Platelet-rich fibrin (PRF) is the second-generation platelet concentrate and represents a slow release system for growth factors. Use of PRF showed promising results in various periodontal surgical procedures. The aim of this report is to describe two-stage treatment of a canine tooth having an infrabony defect accompanied with a deep dehiscence by using PRF-connective tissue graft (CTG) combination. Case Report: A 28-year old man was referred to the Department of Periodontology with chief complaints of purulent exudate formation, tooth mobility in tooth #23 (FDA classification). Deep periodontal pockets in combination with 4 mm buccal recession were detected. Radiographically, a significant radiolucency was also present. CTG graft combined with coronally advanced flap by adding a PRF gel was utilized for the treatment of defect and accompanying gingival recession. Conclusion: Significant improvements were detected at all periodontal clinical and radiographic measurements.